An efficient and flat-gain Erbium-doped fiber amplifier in the region of 1550 nm to 1590 nm - Harun, Sulaiman Wadi; Paul, Mukul Chandra; Pal, Mrinmay; Dhar, Anirban; Sen, Ranjan; Das, S.; Bhadra, Shyamal Kumar; Shahabuddin, Nurul Shahrizan; Ahmad, Harith (INOE, 2008)
A flat gain erbium-doped fiber amplifier (EDFA) operating in the 1550 nm to 1590 nm region is demonstrated. The EDFA uses only a15m EDF as opposed to a standard L-band EDFA which requires significantly longer EDF lengths. The EDF is fabricated using a Modified Chemical Vapor Deposition process in conjunction with a solution doping technique. The NA, cut-off wavelength and erbium ion concentration of the fiber are obtained at 0.15, 998 nm and 900 ppm respectively. The gain of the EDFA is flattened to a level of about 12 dB with a gain variation of less than 3 dB over a range from 1550 to 1590 nm with a 1480nm pump at 90mW. This amplifier operates on the energy transfer of the quasi-two-level system, whereby the C-band energy acts as a pump for the population inversion required for gain at the longer wavelength. The noise figure at the flat gain region varies from 6 to 8.5 dB.